DNA afetivo Kamê e Kanhru: prática artística colaborativa em comunidade Kaingáng - Mallmann, Kalinka Lorenci (2018)
DNA Affective kamê and kanhru refers to a research in visual poetics, involving collaborative artistic practices in community starting from the activation of the specific modes of social organization of the kaingáng indigenous culture through a network of exchanges, connectivity and affections. In this way, we seek to approach the artistic and critical production, which investigates these singular ways of doing and thinking about art, addressing the specificities of these practices and their methodologies. Thus, the contributions of Grant H. Kester and Pablo Helguera are used to problematize collaboration in contemporary art and to correlate these practices with the concept of socially engaged art. In the same way, it refers to the theoretical production of Antonio Lafuente, which allows us to meditate around these emerging collaborative processes and the production of the common. The art actions of the proposed project were carried out in kaingáng territory, in the Terra do Guarita community, in the northwest of the state of RS, from audiovisual creation laboratories. These activities foster the local issues and the protagonism of the community facing an open and dynamic artistic process. An action was also taken in web art that allowed us to think about the connectivity existing in these collaborative processes. In this sense one uses of the reflections of Roy Ascott, among other theoretical references concerning the scope of the art and technology. This dissertation comes to understand that collaborative artistic practices in communities are conceived and constituted in a specific way. In addition to being guided by an ethical, empathetic and supportive sense, attributing meaning to "being together" as a transforming power.